Generalized geodesic convex functions on Riemannian manifolds - Kilicman, Adem; Saleh, Wedad (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
In the present paper, we introduce the generalized geodesic convex functions on Riemannian manifolds and present some of their properties. Based on these properties, the generalized geodesic star-shaped functions are established. Results obtained in this paper may inspire future research in convex analysis on manifolds.